Cuba’s Critical Juncture: Main Challenges - Vegard Bye (Iberoamericana: Nordic Journal of Latin American and Caribbean Studies, 2017)
Cuba is rapidly approaching a critical juncture, where a complete and generational change of leadership is unavoidable (between 2018 and 2021). The country and its Revolution is up against some unavoidable and complicated choices in the coming four years. With the rapidly approaching end of the Castro era, without any clear new leadership structure in sight, and with an apparently unsolvable economic crisis and rapidly shrinking confidence in the political power bloc particularly among the younger generations, a deep legitimacy crisis is looming. What are the principal challenges ahead, and how can and will they be solved?